2019
DOI: 10.31557/apjcp.2019.20.5.1445
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Synthase Reductase-A66G and -C524T Single Nucleotide Polymorphisms and Prostate Cancer: A Case-Control Trial

Abstract: Purpose: Some variations in the sequence of methionine synthase reductase (MTRR) gene can increase the risk of various cancers such as prostate cancer. The aim of this study was to investigate the association between prostate cancer and the MTRR A66G and C524T gene single nucleotide polymorphisms (SNPs) using an in silico analysis. Methods:In this case-control study, 218 Iranian men, including 108 men with prostate cancer and 110 prostate cancer-free men, were enrolled. The MTRR A66G and C524T genotyping was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Our knowledge on the association of cancer and MTRR rs1532268 polymorphism is very limited. It has been reported that MTRR rs1532268 polymorphism was associated with increased risk of prostate cancer [28], while other studies did not reveal any obviously significant differences of MTRR rs1532268 polymorphisms among other cancers. Our finding indicated that patients with MTRR rs1532268 CT/TT genotypes played harmful role on GC prognosis.…”
Section: Discussionmentioning
confidence: 79%
“…Our knowledge on the association of cancer and MTRR rs1532268 polymorphism is very limited. It has been reported that MTRR rs1532268 polymorphism was associated with increased risk of prostate cancer [28], while other studies did not reveal any obviously significant differences of MTRR rs1532268 polymorphisms among other cancers. Our finding indicated that patients with MTRR rs1532268 CT/TT genotypes played harmful role on GC prognosis.…”
Section: Discussionmentioning
confidence: 79%
“…For MTRR A66G meta-analysis, total eight studies with 3,631 cases and 5,076 controls [39, 40, 45, 48, 49, 50, 62, present study]. Out of which, three were Asian, three were Caucasian and two were of mixed ethnicities.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies were conducted to check the association of MTHFR C677T gene polymorphism with the prostate cancer [35][36][37][38][39][40][41][42][43][44][45][46][47]. Very few studies were published, which evaluated MTRR A66G polymorphism as risk for prostate cancer [39,40,[48][49][50]. The results of these studies were contradictory for both the selected (MTHFR C677T and MTRR A66G gene) polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…Other enzymes of the homocysteine metabolic pathway are Methylenetetrahydrofolate Reductase (MTHFR) and Thymidylate Synthase (TS). MTRR is involved in reduction of MTR-cob (II) alamin to MTR-cob (I) alamin, and transform 5-methyltetrahydrofolate to tetrahydrofolate [ 94 , 95 ]. The MTRR 66A > G (rs1801394) polymorphism changes an isoleucine into a methionine (Ile22Met) leading to the reduced enzyme activity [ 96 ].…”
Section: Amino Acid Metabolismmentioning
confidence: 99%